Pharmacokinetics and Safety of Single and Multiple Doses of Peficitinib (ASP015K) in Healthy Chinese Subjects - Gao X; He X; Oshima H; Miyatake D; Otsuka Y; Kato K; Cai C; Wojtkowski T; Song N; Kaneko Y; Shi A (Dove Medical Press, 2022)
Xin Gao,1 Xuemei He,1 Hiroyuki Oshima,2 Daisuke Miyatake,2 Yukio Otsuka,2 Kota Kato,3 Chunxiao Cai,4 Tomasz Wojtkowski,5 Nan Song,6 Yuichiro Kaneko,7 Aixin Shi1 1Clinical Trial Center, Beijing Hospital, National Center of Gerontology; Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 2Clinical Pharmacology and Exploratory Development, Astellas Pharma Inc., Tokyo, Japan; 3Analysis & Pharmacokinetics Research Labs., Astellas Pharma Inc., Ibaraki, Japan; 4Development Medical Department, Astellas (China) Investment Co., Ltd, Beijing, People's Republic of China; 5Data Science Development, Astellas Pharma US, Inc., Northbrook, IL, USA; 6Development Division Biostatistics and Statistical Programming, Astellas (China) Investment Co., Ltd, Beijing, People's Republic of China; 7Biostatistics Group, Japan-Asia Data Science, Development, Astellas Pharma Inc, Tokyo, JapanCorrespondence: Aixin Shi, Clinical Trial Center, Beijing Hospital, National Center of Gerontology; Institute of Geriatric Medicine, Chinese Academy of Medical Science, Beijing, 100730, People's Republic of China, Tel +86-10-85133632, Email aixins0302@126.comObjective: To investigate the pharmacokinetics and safety of peficitinib (Janus kinase inhibitor for the treatment of rheumatoid arthritis) in healthy Chinese subjects following single and multiple doses.Methods: This open-label, randomized study was conducted at one site in China. Subjects received peficitinib 50, 100 or 150 mg as a single dose on Day 1 (fasted) and once daily from Days 8 to 13 in the multiple-dose period (fed). Blood samples were collected before administration each day, and up to 72h post administration. Pharmacokinetic assessments included area under the concentration curve (AUC), half-life (t1/2), maximum concentration (Cmax), and time to maximum concentration (tmax) of peficitinib and its metabolites (H1, H2 and H4). Treatment-emergent adverse events (TEAEs) were evaluated.Results: Thirty-six subjects were enrolled (12 per dose group). After a single dose of peficitinib, median tmax was 1.0- 1.5h and mean t1/2 was 7.4- 13.0h for all doses. In the multiple-dose period, median tmax was 1.5- 2.0h. Dose-proportional increases in Cmax and AUC24h were observed for peficitinib and its metabolites following single and multiple doses, with minimal drug accumulation. The major metabolite was H2, with a systemic exposure of > 150% of the parent AUC. Drug-related TEAEs were experienced by 5 (13.9%) and 12 (33.3%) subjects in the single- and multiple-dose periods, respectively. Following multiple doses of peficitinib, TEAEs were more frequent in higher than lower dose groups but were mild in severity with no related discontinuation or death.Conclusion: Following single and multiple doses of peficitinib in healthy Chinese subjects, peficitinib demonstrated rapid absorption and was well tolerated at all doses.Clinicaltrials.gov Identifier: NCT04143477.Keywords: rheumatoid arthritis, treatment, dose-proportionality, tsDMARDs